القيم بين واقعية الفعل وسلطة المرجع: مقاربة سوسيولوجية في الرواية العربية - الشريف حبيلة (International Institute of Islamic Thought, 2016)
تقارب الدراسة الرواية العربية في علاقتها بالمجتمع وقيمه، ومدى انسجامها مع ما هو سائد من أعراف أسست لها مرجعيات الجماعة التي يكتب لها الكاتب العربي، وذلك بتفكيك الأسس الفكرية المضمرة في النص، سواء وافقت مرجعيات المجتمع أو ناقضتها، وتدفع لتغييرها، ومن ثم بيان كيف يحضر القيمي في الفني؟ وهل للأيديولوجيا سلطة على فعل الكتابة؟ وهل تشكل القيم عنصراً جماليا؟ وكيف يمكن للواقع الحضور في النص الروائي؟ وإلى أي مدى يمكن للكاتب مسايرة الواقع؟ كل هذه الأسئلة تجيب عنها الدراسة باستخدام المنهج السوسيولوجي، الكفيل بمقاربة علاقة الفن الروائي بجدلية الواقع والمرجع. This study approaches Arabic novel in its relation to society and its values, and its compatibility with the prevailing norms in the society that the Arab writer writes for. It dismantles the implicit intellectual foundations in the text, whether they agree with frame of reference of the society or contradict it - with a view of changing it. The study addresses following questions: how values appear in the artistic expression? Does ideology have authority over writing? Do values possess an aesthetics element? How reality appear in text of the novel? To what extent can the writer cope with these realities? The study answers these questions using sociological methodology, as it enables understanding the relationship between art of the novel and dialectics of reality and authority.